In the Universe of Cassandra: The Ancient Topos of Clairvoyance in the Futuristic World of Minority Report (2002) - Budzowska, Małgorzata (Text Matters: A Journal of Literature, Theory and Culture, 2020)
The figure of Cassandra is well-known from numerous representations in ancient and modern literature as an archetype of a woman who has the power to see the future, but whose visions are not believed. In ancient Greek literature, Cassandra was an important character serving as a prophet of an approaching catastrophe. In her modern adaptations, this figure became a metaphor in psychoanalytical research on human moral behaviour (Melanie Klein and the Cassandra complex) developed in feminist writing. Cassandra has also been of interest to filmmakers, with perhaps the best adaptation of the subject of Cassandra’s clairvoyance being Steven Spielberg’s film Minority Report. Loosely based on Philip K. Dick’s 1956 short story The Minority Report, the plot presents a version of the Cassandra myth, in which a woman together with male twins operate as a group mind to predict future crimes. Their visions are used by the state to prevent the crimes and imprison the would-be criminals. This article offers a thorough analysis of all the ancient and modern features of the metaphor of Cassandra employed in this movie within the overarching framework of the central theme of free will vs. determinism. According to this approach, the central theme is examined with reference to ancient Aristotelian and Stoic moral philosophy, the modern feminist psychoanalysis of Melanie Klein, and the political philosophy and legal issues in the post-9/11 world.